Discussion on Improving the Level of Enterprise Business Administration Under the New Economic Environment - Tang, Baocheng (International Journal of Global Economics and Management, 2024)
In the ever-evolving landscape of the new economy, businesses are confronted with numerous challenges and opportunities. This article examines three key aspects: technological innovation, market competition, and regulatory updates, and their impact on enterprise business administration. Firstly, technological innovation drives digital transformation, necessitating the active application of technologies such as artificial intelligence and big data to enhance efficiency. Secondly, intensifying market competition, coupled with the rise of new industries and global competitive pressures, calls for enterprises to expand their talent pool and strengthen management and innovation. Lastly, the continuous update of laws and regulations requires businesses to establish robust risk management systems, enhance compliance awareness, and ensure legal operations. In conclusion, by comprehensively addressing challenges in technology, market dynamics, and legal compliance, businesses can enhance their business administration levels to meet the demands of the evolving new economic environment.